2021
DOI: 10.21037/atm-20-5540
|View full text |Cite
|
Sign up to set email alerts
|

Late response to rosuvastatin and statin-related myalgia due to SLCO1B1, SLCO1B3, ABCB11, and CYP3A5 variants in a patient with Familial Hypercholesterolemia: a case report

Abstract: Statins are the most widely used cholesterol-lowering drugs for cardiovascular diseases prevention.However, some patients are refractory to treatment, whereas others experience statin-related adverse events (SRAE). It has been increasingly important to identify pharmacogenetic biomarkers for predicting statin response and adverse events. This case report describes a female patient with familial hypercholesterolemia (FH) who showed late response to rosuvastatin and experienced myalgia on statin treatment. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The SLCO1B3 gene rs4149117 and rs7311358 polymorphisms have been shown to affect the efficacy of statin treatment in patients with hypercholesterolemia. Additionally, these polymorphisms are associated with an increased risk for acute rejection and allograft failure in lung transplant recipients treated with mycophenolic acid [ 31 , 32 ]. To date, the above polymorphisms have not been investigated in relation to diseases of the liver and the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The SLCO1B3 gene rs4149117 and rs7311358 polymorphisms have been shown to affect the efficacy of statin treatment in patients with hypercholesterolemia. Additionally, these polymorphisms are associated with an increased risk for acute rejection and allograft failure in lung transplant recipients treated with mycophenolic acid [ 31 , 32 ]. To date, the above polymorphisms have not been investigated in relation to diseases of the liver and the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the ATP-binding cassette transmembrane mediator (ABC) have been significantly correlated with impaired efflux of statins as well as cholesterols from cells. The attenuated activity of ABCA1, ABCA11, and ABCG2 was found to reduce the excretion of statin and increase its intrahepatic levels, thereby increasing hepatotoxicity as well as myopathy to statin adverse consequences [41,52]. Oral lipid-antagonists enter the circulatory system via the enteric SLC and ABC gene-transporters.…”
Section: Snps Linked To Pharmacokinetics and Pharmacotoxicity Of Statins In Fhmentioning
confidence: 99%
“…The hepatic absorption of statins is mediated primarily by the solute carrier organic anion transporter 1B1 (encoded via SLCO1B1 ). Loss-of-function SLCO1B1 *5 (c.521T>C) and SLCO1B1 *1B (c.388A>G) SNPs remarkably diminish plasma LDL-C transporting to the liver and raise the systemic exposure to statin [ 52 ]. This results in a greater incidence of rhabdomyolysis risk and a negligible cholesterol optimizing effect.…”
Section: Pharmacogenomics Of Statin In Fhmentioning
confidence: 99%
See 1 more Smart Citation
“…SLCO1B1 rs2306283 (c.388A>G), for example, was associated with a more pronounced reduction in LDL-c after treatment with atorvastatin and may be a predictor of therapeutic response [ 15 ]. We also recently found that SLCO1B1*15 and variants in SLCO1B3 and ABCB11 delayed rosuvastatin response in an FH patient, without jeopardizing LDL-c reduction after 12 weeks of treatment [ 16 ]. Furthermore, variants in drug-metabolizing enzymes, such as CYP3A4*22 , have been associated with higher LDL-c reduction [ 17 ], whereas our group reported that CYP3A5*3 (rs776746) was associated with a lower reduction in total cholesterol, LDL-c, and HDL cholesterol (HDL-c) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%